Applying quality principles to Australian university transnational teaching and learning : final report 2013. - Pyvis, David (Australia. Office for Learning and Teaching, 2013)
This report describes a project to apply a framework of quality principles to Australian university transnational teaching and learning, that is, to educational practices in Australian university programmes delivered and conducted 'offshore'. It outlines the broad aim of the project to provide quality enhancement of Australian transnational higher education through the implementation of principles of quality to inform transnational teaching and learning practice. The report outlines the partnering of four universities in a collaborative and participatory approach to enlist universities in developing applications of the Quality Principles effective for their educational delivery styles and approaches. The outcomes of the project are reported and recommendations are outlined. [Executive summary, ed]